1992
DOI: 10.1073/pnas.89.18.8472
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification and reconstitution of the human multidrug-resistance pump: characterization of the drug-stimulatable ATP hydrolysis.

Abstract: Multidrug-resistant human tumor cells overexpress the MDRI gene product P-glycoprotein, which is believed to function as an ATP-dependent efflux pump. In this study we demonstrate that the partially purified P-glycoprotein, when reconstituted in an artificial membrane, catalyzes drug-stimulated ATP hydrolysis. Plasma membrane proteins of a human multidrug-resistant cell line, KB-V1, were solubilized with 1.4% (wt/Vol) ocyl 3-D-glucopyranoside in the presence of 0.4% phospholipid and 20% (vol/vol) glycerol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
227
1
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 380 publications
(247 citation statements)
references
References 33 publications
18
227
1
1
Order By: Relevance
“…Reaction intermediates have affinities 10 10 to 10 15 times higher than the corresponding Michaelis-Menten complexes (16), reflected in the K m . The K m (ATP) for human Pgp is 0.3-1.0 mM (9,25,33,40). Following trapping of 2.5 M 8-azido-[␣-32 P]ATP in the mutant Pgp, we found that 75 mM ATP (a 30,000-fold excess) could only displace ϳ20% of the label (data not given).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reaction intermediates have affinities 10 10 to 10 15 times higher than the corresponding Michaelis-Menten complexes (16), reflected in the K m . The K m (ATP) for human Pgp is 0.3-1.0 mM (9,25,33,40). Following trapping of 2.5 M 8-azido-[␣-32 P]ATP in the mutant Pgp, we found that 75 mM ATP (a 30,000-fold excess) could only displace ϳ20% of the label (data not given).…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type Pgp also occludes the nucleotide, but it is [␣-32 P]ADP that is trapped and only in the presence of Vi. It is well established that wild-type Pgp has a relatively low affinity for ATP (25,32,33), but the conformational changes that accompany ATP hydroly- The reaction was stopped by adding 0.1 ml of ice-cold ATPase buffer containing 10 mM ATP and 1 M NaCl. The nucleotides and proteoliposomes were separated using a G-50 column, as described under "Experimental Procedures."…”
Section: The Mutant Pgp E556q/e1201q Exhibits Very Low Levels Of Atpmentioning
confidence: 99%
See 3 more Smart Citations